2022
DOI: 10.1101/2022.07.12.22277556
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

APOEε4 carriership associates with microglial activation independently of Aβ plaques and tau tangles

Abstract: Microglial activation is an early phenomenon in Alzheimer′s disease (AD) that may occur prior to and independently of amyloid-β (Aβ) aggregation. Recent studies in transgenic animal models suggest that the apolipoprotein E ϵ4 (APOEϵ4) allele may be a culprit of early microglial activation in AD. However, it is unclear whether the APOEϵ4 genotype is associated with microglial reactivity in the living human brain. Here, we tested whether APOEϵ4 carriership is associated with microglial activation in individuals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 80 publications
0
12
0
Order By: Relevance
“…Glial activation, tau, and neurodegenerative pathology first appear in the MTL and then spread to involve other cortical areas as cholinergic denervation becomes more widespread ( Figure 7A ). Across the aging and AD spectrum, APOEɛ4 carriers present increased microglial activation in early Braak stage regions within the MTL compared to noncarriers, which mediates Aβ-independent effects of APOEɛ4 on tau accumulation (62). The rapidly progressing limbic-amnestic phenotype indexes the spreading of pathology that is responsible for ushering APOEɛ4 carriers through prodromal stages of disease and over the dementia threshold, with a response to acetylcholinesterase-inhibitors (AChE-Is) that is apparent in the mild stage of AD (63).…”
Section: Discussionmentioning
confidence: 99%
“…Glial activation, tau, and neurodegenerative pathology first appear in the MTL and then spread to involve other cortical areas as cholinergic denervation becomes more widespread ( Figure 7A ). Across the aging and AD spectrum, APOEɛ4 carriers present increased microglial activation in early Braak stage regions within the MTL compared to noncarriers, which mediates Aβ-independent effects of APOEɛ4 on tau accumulation (62). The rapidly progressing limbic-amnestic phenotype indexes the spreading of pathology that is responsible for ushering APOEɛ4 carriers through prodromal stages of disease and over the dementia threshold, with a response to acetylcholinesterase-inhibitors (AChE-Is) that is apparent in the mild stage of AD (63).…”
Section: Discussionmentioning
confidence: 99%
“…The advantage is that epicenter locations can be individually determined and thus allow for patient-tailored prediction of tau-PET patterns rather than relying on categorical subtyping, where the assignment of individuals to subtypes can be ambiguous. Second, for mapping gene expression, we focused in a hypothesis-driven manner on the MAPT gene, but we caution that the expression patterns of APOE, 58,59 or other yet-to-be-identified genes, may show similar or even stronger spatial similarity to tau-PET. However, given the large number of potential genes, an exploratory analysis bears the risk of overfitting and would require extensive cross-validation, which was beyond the scope of the current study.…”
Section: Discussionmentioning
confidence: 99%
“…The [ 11 C]PBR28 signal is negligible in individuals with low-affinity binding, while those with mixed affinity show a heterogeneous tracer signal . Thus, mixed- and low-affinity binders were excluded from the study to decrease the noise associated with artificial uptake variations . Importantly, previous studies have found no difference in AD biomarkers across different affinity groups .…”
Section: Methodsmentioning
confidence: 99%